2018
DOI: 10.1038/s41467-018-07284-w
|View full text |Cite
|
Sign up to set email alerts
|

Over 1000-fold enhancement of upconversion luminescence using water-dispersible metal-insulator-metal nanostructures

Abstract: Rare-earth activated upconversion nanoparticles (UCNPs) are receiving renewed attention for use in bioimaging due to their exceptional photostability and low cytotoxicity. Often, these nanoparticles are attached to plasmonic nanostructures to enhance their photoluminescence (PL) emission. However, current wet-chemistry techniques suffer from large inhomogeneity and thus low enhancement is achieved. In this paper, we report lithographically fabricated metal-insulator-metal (MIM) nanostructures that show over 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 53 publications
0
103
0
Order By: Relevance
“…Given the distance-dependent plasmon-enhanced upconversion, the structure and shape of plasmonic materials in the form of sphere, rod, pillar/hole array, and core–shell particle need to be exquisitely designed to maximize the upconversion enhancement. 43,45,50…”
Section: Fundamentalsmentioning
confidence: 99%
“…Given the distance-dependent plasmon-enhanced upconversion, the structure and shape of plasmonic materials in the form of sphere, rod, pillar/hole array, and core–shell particle need to be exquisitely designed to maximize the upconversion enhancement. 43,45,50…”
Section: Fundamentalsmentioning
confidence: 99%
“…However, in sections 3.1 and 4.1, the emission intensity was seen to decrease when RE 2 Ti 2 O 7 showed a linear shape. The reason is considered to be related to the shape of RE 2 Ti 2 O 7 because there is an example in which the phosphor is finely patterned to improve the emission intensity [12].The evidence presented in section 4.2 suggests that RE 2 Ti 2 O 7 may be a luminescent compound. Therefore, in our future research, we intend to fabricate a thin film UC phosphor that emits high-intensity light.…”
Section: Cross-sectional Stem Image and Elemental Mappingmentioning
confidence: 99%
“…In recent years, the materials and technology required for the synthesis of UC phosphors have attracted considerable attention. In 2018, Das et al reported metal-insulator-metal nanostructures that show over a thousand-fold increase in their photoluminescence (PL) [12]; in early 2019, Jadczak et al demonstrated a room temperature UC PL process in a monolayer semiconductor WS 2 [13]. The latest developments include a unique study by Gupta et al, who demonstrated that UC nanoparticles fluoresce 50 times more on a gold coated cicada wing [14].…”
Section: Introductionmentioning
confidence: 99%
“…The typical upconversion nanocrystals (UCNCs) is NaYF 4 single crystalline hexagonal phase host matrix co‐doped with sensitizer (donor) Yb 3+ and activator (acceptor) Er 3+ rare earth trivalent lanthanide ions . The UCNCs are promising luminescent nanomaterials which exhibit peculiar physiochemical attributes, including large anti‐Stoke shift, minimal autofluorescence background, narrow emission bandwidths, deep penetration depth into tissue sample, and low cytotoxicity. UCNCs have a limitation of the very low intrinsic photon conversion efficiency typically lower than 1% owing to the low extinction coefficient of lanthanide dopants …”
Section: Acknowledgmentsmentioning
confidence: 99%